Association of C677T polymorphism (rs1801133) in MTHFR gene with depression - Rai, V. (Cellular and Molecular Biology, 2017)
Depression is one of the mental disorders with a state of low mood and aversion to activities that exerts a negative effect on a person's thoughts and behavior. Genetic association studies on MTHFR C677T polymorphism and depression have been repeatedly performed over the last two decades, but results are inconsistent. The aim of the present study was to assess the relationship between MTHFR C677T polymorphism and depression by literature review and meta-analysis. Four electronic databases, PubMed, Google Scholar, Science direct and Springer Link were searched for case control articles focusing on MTHFR C677T polymorphism and the risk of depression. A total of 30 studies including 4,802 cases and 17,362 controls were involved in present meta-analysis. When all the eligible studies were pooled into this meta-analysis,  significant association between depression risk and MTHFR C677T polymorphism was found in three genetic models (Additive model: OR T vs C= 1.20, 95 % CI= 1.00-1.34, p=0.0004; homozygote model: OR TT vs.CC=1.37, 95% CI= 1.13-1.65, p=0.0004; dominant model: OR TT+CT vs CC=1.13, 95 % CI= 0.99-1.28, p=0.04), while meta-analysis with other two genetic models did not show association with other two genetic models ( recessive model: OR TT vs CT+CC= 1.36, 95 % CI = 0.91-2.04, p=0.13; co-dominant model: OR CT vs CC=1.00, 95 % CI=0.93-1.08,p=0.84). Present meta-analysis supports that there is a meager significant association between MTHFR C677T polymorphism and depression risk.